The pharmacological challenges of treating tuberculosis and HIV coinfections. Issue 2 (1st February 2017) - Egelund, Eric F.; Dupree, Lori; Huesgen, Emily; Peloquin, Charles A.
ABSTRACT: Introduction : Tuberculosis (TB) is the most prevalent opportunistic infection among HIV patients, and the leading cause of death among HIV patients worldwide. Simultaneous treatment of both diseases is recommended by current guidelines, but can be challenging due to the potential for drug-drug interactions, overlapping toxicities, difficulty adhering to medications, and an increased risk for immune reconstitution inflammatory syndrome (IRIS). Clinical manifestations of TB can also vary between HIV-infected patients and uninfected patients, which can increase the risk for delayed diagnosis. Areas covered : Topics covered in this review include the following: the inter-related pathophysiology of HIV and TB; clinical manifestations and diagnosis; drug-drug interactions, particularly the rifamycins with the antiretrovirals; IRIS presentation and treatment, as well as a discussion on overlapping toxicity between the two disease states. Expert commentary : The complexity of managing these two disease states simultaneously requires a multidisciplinary approach to care and dedicated resources. If properly funded, TB/HIV co-infection will continue to decline over the coming years.